From Learning to Memory: What Flies Can Tell Us about Intellectual Disability Treatment - Androschuk, Alaura; Al-Jabri, Basma; Bolduc, Francois V. (Frontiers in Psychiatry, 2015)
Intellectual disability (ID), previously known as mental retardation, affects 3 % of the population and remains without pharmacological treatment. ID is characterized by impaired general mental abilities with associated defects in adaptive function in which onset occurs before 18 years old. In severe ID, genetic causes are increasingly recognized in large part due to genome-wide techniques such as microarrays and exome sequencing. Unfortunately drug discovery for treatment of ID has not followed the same pace as gene discovery, leaving clinicians, patients and families without the ability to ameliorate symptoms. Despite this, several model organisms have proven valuable in developing and screening candidate drugs. One such model organism is the fruit fly Drosophila. First, we review the current understanding of memory in human and its model in Drosophila. Second, we describe key signaling pathways involved in ID and memory such as the cAMP-CREB pathway, the regulation of protein synthesis, the role of receptors and anchoring proteins, the role of neuronal proliferation, and finally the role of neurotransmitters. Third, we characterize the types of memory defects found in patients with ID. Finally, we discuss how important insights gained from Drosophila learning and memory could be translated in clinical research to lead to better treatment development.